2010
DOI: 10.1507/endocrj.k10e-196
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgery for primary hyperparathyroidism with or without intraoperative parathyroid hormone monitoring

Abstract: Bilateral neck exploration, the identification of all parathyroid glands and removal of all abnormal glands, has traditionally been regarded as the standard surgical strategy for the treatment of primary hyperparathyroidism (pHPT) [1][2][3][4]. However, in recent years, several investigators have questioned the routine performance of bilateral neck exploration because the cause of pHPT in most patients is a single parathyroid adenoma and preoperative imaging tests, such as Technetium-99m sestamibi scans and ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…We also tested the adequacy of the resection using IOPTH determination. As reported before, IOPTH increases the success rate of parathyroid surgery [13]. Blue dyes and especially methylene blue are used intravenously for the localization of parathyroid tumors [14].…”
Section: Discussionmentioning
confidence: 82%
“…We also tested the adequacy of the resection using IOPTH determination. As reported before, IOPTH increases the success rate of parathyroid surgery [13]. Blue dyes and especially methylene blue are used intravenously for the localization of parathyroid tumors [14].…”
Section: Discussionmentioning
confidence: 82%
“…Failure to detect SPA was between 1-2.7% in patients examined by both 99mTc-MIBI PS and USG, without intra-operative QPTH monitoring (12,27,28). In Kiminori et al’s study, while the cure rate was 93.1% in MIP without intra-operative QPTH measurements; in MIP with QPTH measurement, the cure was 97,5% and revealed that QPTH measurement can elicit especially the PS negative Pas determination (29). …”
Section: Discussionmentioning
confidence: 92%
“…[8][9][10] Some studies have found value in the use of IOPTH in all cases of focused exploration. 11 Others have found minimal benefit in cases of preoperative concordance, and they reserve the role of IOPTH for discordant or negative preoperative imaging. 12 The cost to benefit ratio of the IOPTH assay remains questionable.…”
Section: See Invited Critique At End Of Articlementioning
confidence: 99%